Gender norms and income misreporting within households - Anja Roth; Michaela Slotwinski (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
We show that the discontinuity in the distribution of surveyed female income shares at the margin where a woman would outearn her partner is primarily driven by norm induced misreporting in surveys. We draw on unique Swiss data combining survey and administrative information for the same individual and their partner. We demonstrate that individuals misreport incomes in surveys to comply with the male breadwinner norm. The male breadwinner norm does, however, not affect real labor market decisions around this margin. The resulting survey bias leads to a considerable overestimation of policy relevant measures like the gender wage gap.
Keywords: D10; J01; J16; 330; gender norms; female income shares; combination survey and administrative data; income misreporting; gender earnings gap